2012
DOI: 10.1177/2042018812454322
|View full text |Cite
|
Sign up to set email alerts
|

Licorice abuse: time to send a warning message

Abstract: Licorice extract has always been recognized as a sweetener and a thirst quencher. Its nutritive value is overrated by many who consume significant amounts and are prone to complications. Glycyrrhetic acid, the active metabolite in licorice, inhibits the enzyme 11-ß-hydroxysteroid dehydrogenase enzyme type 2 with a resultant cortisol-induced mineralocorticoid effect and the tendency towards the elevation of sodium and reduction of potassium levels. This aldosterone-like action is the fundamental basis for under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
160
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(196 citation statements)
references
References 80 publications
0
160
0
12
Order By: Relevance
“…A high dose of GLC also affects the retention of water and salt in GLC-treated rats, which is due at least in part to the increased expression of aquaporin 2 and 3 water channels in the renal inner and outer medulla of the kidney, which may be associated with the mineralocorticoid receptor [35,36] . Previous studies have reported that a higher dose of GLC administration (200 mg/kg/day) ameliorates both renal function defects, especially the renal concentrating ability, and structural lesions in renal tissues in rats in the early-phase of ischemia-induced acute renal failure [37] .…”
Section: Discussionmentioning
confidence: 99%
“…A high dose of GLC also affects the retention of water and salt in GLC-treated rats, which is due at least in part to the increased expression of aquaporin 2 and 3 water channels in the renal inner and outer medulla of the kidney, which may be associated with the mineralocorticoid receptor [35,36] . Previous studies have reported that a higher dose of GLC administration (200 mg/kg/day) ameliorates both renal function defects, especially the renal concentrating ability, and structural lesions in renal tissues in rats in the early-phase of ischemia-induced acute renal failure [37] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, licorice could lower the risk of apthous ulcers caused by anti-inflammatory drugs like aspirin (2); reduce side effects of spironolactone (3); improve the efficacy and lower the adverse effects of glucocorticoids (4); improve excretion rates and decrease side effects of nitrofurantoin in patients with urinary tract infections (5); and treat cough, asthma, and gastric ulcer during chemotherapies (6). While licorice shows synergistic effects with some drugs, it could also decrease the therapeutic effects of other drugs, or even lead to side effects (7,8). One major reason for these herb-drug interactions (HDI) is cytochrome P450 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Of its 2 isomers, α-GL seems to show a lower incidence of adverse eff ects which encouraged us to compare the PK profi les and adverse eff ects of α-and β-GL when administered separately. Pseudoaldosteronism is the major adverse eff ect of GL which can be severe or even fatal if ignored [ 15 ] . It is mainly caused by GA and 3MGA, the major metabolites of GL, and accordingly, the metabolism of α-and β-GL will dictate the relative safety of the 2 compounds.…”
Section: Discussionmentioning
confidence: 99%